Analisis Potensi dan Kontribusi Subsektor Peternakan terhadap Sektor Pertanian dan Perekonomian di Indonesia - Melianti Nasution; Firmansyah Firmansyah; Afriani H; Fachroerrozi Hoesni; Dodi Devitriano; Farizal Farizal (Jurnal Ilmiah Universitas Batanghari Jambi, 2026)
This study aims to determine the potential, contribution, growth, and relationship of subsectors to the agricultural sector and the economy, as well as the differences in potential, contribution, and growth of the livestock subsector to the agricultural sector and the economy. This study was conducted over a one-month period using descriptive quantitative methods using secondary data. The data collected were taken from BPS (Central Statistics Agency). The results of the study show that the potential of the livestock subsector in Indonesia with an average IKS value reaching between 0.0164 to 0.0418, all of which are categorized as "not reliable", the contribution of the livestock subsector to the agricultural sector is relatively lower compared to other subsectors with an average of 15.35%, the contribution of the livestock subsector to the economy is relatively lower compared to other subsectors with an average of 1.64%, and the growth of the livestock subsector to the GDP subsector is quite good but not yet dominant with an average of 4.29%. The potential and contribution of the livestock subsector are different compared to other subsectors such as food crops, plantation crops, forestry, and fisheries. Meanwhile, in terms of growth rate, the livestock subsector shows a significant difference with food crops, forestry, and fisheries, while there is no significant difference in the plantation crop subsector.